Loss of non-muscle myosin II Zipper leads to apoptosis-induced compensatory proliferation in Drosophila. - Verma, D.; Sarkar, B.; Singh, J.; Singh, A.; Mutsuddi, M.; Mukherjee, A. (Biochimica et biophysica acta. Molecular cell research., 2025)
Drosophila Non-muscle myosin II Zipper (Zip) belongs to a functionally divergent class of molecular motors that play a vital role in various cellular processes including cell adhesion, cell migration, cell protrusion, and maintenance of polarity via its cross-linking property with actin. To further determine its role in cell proliferation and apoptosis, we carried out Zip loss of function studies that led to compromised epithelial integrity in Drosophila wing imaginal discs as evident from the perturbed expression pattern of cell-cell junction proteins Cadherin, Actin, and Armadillo. Disruption of these adhesion proteins resulted in the cells undergoing apoptosis as evident from the increased level of effector caspase, cDcp-1. The induction of cell death due to the loss of function of Zip was accompanied by proliferation as apparent from increased PH3 staining. The control of apoptosis-induced compensatory proliferation lies under the caspase cascade. We carried out experiments that suggested that the apical caspase Dronc is responsible for the apoptosis-induced compensatory proliferation due to the loss of Zip function and not the effector caspase Drice/Dcp-1. Further, it was observed that Dronc leads to the subsequent activation of Jun N-terminal kinase pathway (JNK) pathway and Wingless (Wg) mitogen that diffuse to the neighboring cells and prompt them to undergo cell division. Taken together, our results suggest that loss of function of Zip leads to apoptosis-induced compensatory proliferation.